Proceedings of the Seventieth Regular Meeting of the Rocky Mountain Coal Mining Institute Steamboat Village Inn, Steamboat Springs, Colorado June 30 - July 3,1974 - Morning Session - Monday, July 1,1974 (Rocky Mountain Coal Mining Institute, 1974)
The 70th Regular Meeting of the Rocky Mountain Coal Mining Institute convened at the Steamboat Village Inn, Steamboat Springs, Colorado, and was in session at 10:00 a.m. The session was called to order by Past President O. F. Lewis. Consultant, Colowyo Coal Co., Denver, Colorado. Mr. Lewis introduced President A. F. Geiger, Manager, Navajo Mine, Utah International, Inc., Fruitland, New Mexico. Following are Mr. Lewis' remarks: Ladies and gentlemen, members of the institute, guests and friends, welcome to Steamboat Springs and the 70th meeting of the Rocky Mountain Coal Mining Institute. From all appearances this is our largest meeting and should be the most successful. When I last spoke to you I was President of Colowyo Coal Company and the Rocky Mountain Coal Institute but that has changed. Colowyo Coal Company was acquired last Dec. by W. R. Grace & Co. and operates as Colowyo Coal Company, Division of W. R. Grace & Co. I am confident these people will make a worthwhile contribution to the coal Industry.